Wanted: UX Specialist with Reference Preparation or Reference Classes Assist Students in Preparing for UX Careers. Issue 1 (2nd January 2018) - Roy, Loriene; Kennedy Hallmark, Elizabeth; Gilbert, Sarah
ABSTRACT: One of the most versatile and dynamic career paths available to information specialists is that of UX or user experiences. Graduate students seeking careers in UX may benefit by enrolling in and completing a basic reference class. This article provides support for this option through the reflections of a faculty member teaching reference courses, a UX specialist who was one of her students, and the director of career services who helps students and apply for UX positions and others in the information fields.